2003
DOI: 10.1117/12.483548
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional active contour model for characterization of solid breast masses on three-dimensional ultrasound images

Abstract: The accuracy of discrimination between malignant and benign solid breast masses on ultrasound images may be improved by using computer-aided diagnosis and 3-D information. The purpose of this study was to develop automated 3-D segmentation and classification methods for 3-D ultrasound images, and to compare the classification accuracy based on 2-D and 3-D segmentation techniques. The 3-D volumes were recorded by translating the transducer across the lesion in the z-direction while conventional 2-D images were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Our results indicated that the use of this term increased the accuracy of 3D segmentation. 16 Figure 5 shows the result of the 3D segmentation algorithm for five consecutive slices of a mass.…”
Section: Figurementioning
confidence: 99%
“…Our results indicated that the use of this term increased the accuracy of 3D segmentation. 16 Figure 5 shows the result of the 3D segmentation algorithm for five consecutive slices of a mass.…”
Section: Figurementioning
confidence: 99%
“…In [54,55], Madabhushi et al proposed a fully automatic approach for BUS image segmentation using PDM which is initialized by utilizing the boundary points produced in tumor localization step. In [56,57], Sahiner applied PDM for 3D BUS tumor segmentation, the external forces had two terms: the first term was defined on image gradient by using 3×3 Sobel filters, and the second term is the balloon force. In [58,59],…”
Section: Deformable Models For Bus Image Segmentationmentioning
confidence: 99%